PREVALENSI KECACINGAN Ascaris lumbricoides PADA ANAK SEKOLAH DASAR DI DESA NELAYAN INDAH KECAMATAN MEDAN LABUHAN - Riwayati, Riwayati (Universitas Negeri Medan, 2013)
ABSTRACTThis study aims to determine the prevalence of intestinal worms and Ascaris lumbricoides infection rate in primary school children in Nelayan Indah Village Medan Labuhan Sub-District. Samples from this study were primary school children classes I up grade VI as many as 50 people. Quantitative fecal examination performed using Stoll dilution method. The results showed that the worm prevalensi Ascaris lumbricoides age group of 6-9 years was 100% and the age group 10-13 years was 96%. Ascaris lumbricoides worm infection rate in primary school children in Nelayan Indah Village Medan Labuhan District belong to the classification of sub-field loss clinics. Kata Kunci : Prevalensi kecacingan, anak Sekolah Dasar.